PENINGKATAN PEMAHAMAN KONSEP IKATAN KIMIA MELALUI PERBAIKAN BAHAN AJAR - Agus Mukti Wibowo (FKIP USK, 2013)
Most of the materials in chemical bond are abstract concepts such as ions, ionic radii and orbital. Concepts are considerably difficult to be studied by students who have not had formal thinking ability. This difficulty may be caused error concept, namely the concept of student understanding is different from the agreement by experts. One source of error is the concept of the textbooks used in the learning process. Inproper emplanation or inadequate chemical bonds in the material in the books or high school chemistry teaching materials can lead to errors in sudent. The remedial concept using materials that have been corrected his mistakes and shortcomings plus can reduce errors that occur in students' concept.